Associations of family meal frequency with family meal habits and meal preparation characteristics among families of youth with type 1 diabetes. Issue 3 (4th June 2013) - Kornides, M. L.; Nansel, T. R.; Quick, V.; Haynie, D. L.; Lipsky, L. M.; Laffel, L. M. B.; Mehta, S. N.
Abstract Background While benefits of family mealtimes, such as improved dietary quality and increased family communication, have been well‐documented in the general population, less is known about family meal habits that contribute to more frequent family meals in youth with type 1 diabetes. Methods This cross‐sectional study surveyed 282 youth ages 8–18 years with type 1 diabetes and their parents on measures regarding diabetes‐related and dietary behaviours. T‐tests determined significant differences in youth's diet quality, adherence to diabetes management and glycaemic control between those with and without regular family meals (defined as ≥5 meals per week). Logistic regression analyses determined unadjusted and adjusted associations of age, socio‐demographics, family meal habits, and family meal preparation characteristics with regular family meals. Results 57% of parents reported having regular family meals. Families with regular family meals had significantly better diet quality as measured by the Healthy Eating Index (P < 0.05) and the NRF9.3 (P < 0.01), and adherence to diabetes management (P < 0.001); the difference in glycaemic control approached statistical significance (P = 0.06). Priority placed on, pleasant atmosphere and greater structure around family meals were each associated with regular family meals (P < 0.05). Meals prepared at home were positively associated with regular family meals, while convenience and fast foods were negatively associated (P < 0.05). Families in which at least one parent worked part‐time or stayed at home were significantly more likely to have regular family meals than families in which both parents worked full‐time (P < 0.05). In the multivariate logistic regression model, greater parental priority given to family mealtimes (P < 0.001) and more home‐prepared meals (P < 0.001) predicted occurrence of regular family meals; adjusting for parent work status and other family meal habits. Conclusions Strategies for promoting families meals should not only highlight the benefits of family meals, but also facilitate parents' skills for and barriers to home‐prepared meals.